Is the policy environment for Zambia supportive of a thriving whole-of-government monitoring and evaluation system? - Kanyamuna, Vincent (Advances in Social Sciences Research Journal, 2020)
A whole-of-government monitoring and evaluation system (WoGM&ES) is a robust system that not only provides an integrated and all-encompassing framework of M&E practices, principles and standards to be used throughout government institutional structures, but also functions as an apex-level system for information and draws from the component systems in a framework meant to deliver essential M&E products tailored to satisfy information needs of users [1]. To implement a successful WoGM&ES, a supportive policy environment is crucial for any organisation, governments inclusive. The Zambian government is currently rolling out an ambitious WoGM&ES to strengthen its public sector accountability, feedback and learning functions. It was the objective of this study to investigate the policy environment in Zambia in respect of M&E practice in the public sector. In that regard, particular policy aspects were considered and these included assessing the availability of an M&E plan; whether the difference between M (monitoring) and E (evaluation) was recognised; and if the need for M&E autonomy and impartiality was mentioned. Others were to determine if feedback mechanisms were explicit as well as whether there was integration of M&E results in planning and budgeting processes. The study findings have shown that the policy environment to support a thriving M&E practice in the Zambian public sector was still fragmented and weak. While efforts by government to put policy measures were in place, evidence of transformational shift to implement these measures remained weak. However, it is promising that, in many ways, Zambia was on the right path regarding the introduction and articulation of policy provisions in support of M&E and broadly in promoting a culture of results.